2005
DOI: 10.2460/javma.2005.226.418
|View full text |Cite
|
Sign up to set email alerts
|

Heel bulb lacerations in horses: 101 cases (1988–1994)

Abstract: Horses that sustain heel bulb lacerations can successfully return to their intended use. Involvement of the distal interphalangeal joint is associated with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 8 publications
3
29
1
Order By: Relevance
“…Antibiotics can be administered by direct administration into the cavity by periodic injection or by continuous lavage delivery system, by regional intravenous or interosseus perfusion, by impregnated polymethylacrylate beads or biodegradable hydroxyapatite cement or dextran gel, by antibiotic impregnated cellulose sponge, and systemically. Vascular injury or thrombosis limits the delivery of systematically administered antibiotics and regional limb perfusion should be considered to deliver an antimicrobial under pressure to a selected region of the limb (Janicek et al 2005). In this case, the wound was debrided, thoroughly flushed during the whole procedure and antibiotics were administered intra-operatively by regional limb perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics can be administered by direct administration into the cavity by periodic injection or by continuous lavage delivery system, by regional intravenous or interosseus perfusion, by impregnated polymethylacrylate beads or biodegradable hydroxyapatite cement or dextran gel, by antibiotic impregnated cellulose sponge, and systemically. Vascular injury or thrombosis limits the delivery of systematically administered antibiotics and regional limb perfusion should be considered to deliver an antimicrobial under pressure to a selected region of the limb (Janicek et al 2005). In this case, the wound was debrided, thoroughly flushed during the whole procedure and antibiotics were administered intra-operatively by regional limb perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study, the outcome was considered successful (survival without residual lameness) in 109 of 150 horses (72.7%) with contaminated and infected synovial cavities (Pille et al 2009). Severe or chronic infections are more difficult to treat because of the vascular thrombosis, ischaemia and tissue necrosis that accompany these injuries (Janicek et al 2005). …”
mentioning
confidence: 99%
“…The chronicity of the trauma, the amount of tissue lost, and the degree of contamination or infection, will dictate the mode of treatment in each situation (Janicek et al 2005). If no vital structures (such as the coffin joint or tendon sheath) are damaged and the coronary band is stabilized, horses with lacerations of the coronary band have a good prognosis for healing and to return to their intended use.…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining 10 horses, 6 were euthanased and 4 were chronically lame. Overall 18 % of the cases treated developed a hoof wall defect and 7 % resulted in a chronic wound (Janicek et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The management of distal limb wounds is complicated by several factors: increased risk of wound contamination and infection, 2,3 involvement of the coronary corium leading to abnormal hoof wall growth, 4,5 frequent involvement of tendon sheaths, bursae and joint cavities, and excessive motion because of the constant limb loading, which results in the development of excessive granulation tissue formation 2 . Previous studies have reported a poorer prognosis for return to athleticism for wounds involving synovial structures when compared with those without synovial involvement 6,7 . Rapid and effective treatment is essential to prevent permanent damage of contaminated synovial structures 8–12 …”
mentioning
confidence: 99%